RAUDHATUL ATHFAL TEACHER DEVELOPMENT: A CASE STUDY IN NORTH JAKARTA - Hasyim Hasyim; Raihan Raihan; Syahrullah Syahrullah (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the development patterns of Raudhatul Athfal (RA) teachers in North Jakarta, focusing on forms, strategies, and implementation, while identifying factors that support or hinder the process. Using a qualitative case study approach, data were collected through interviews, observation, and documentation. Findings reveal that teacher development occurs through pedagogical training, academic supervision, Teacher Working Group (KKG) forums, and ongoing mentoring, fostering professionalism, reflective practice, and child-centered learning. The study highlights the importance of collaborative, tiered coaching for enhancing teacher competencies and the quality of early childhood education in urban Islamic settings